A Comparison of Performance of ADM1 and Monod Model Treating Low Strength Wastewater. (2016) - Singh, Vidya; Pandey, N.D.
Abstract: In the present paper, for performance evaluation two model namely anaerobic digestion model 1 and Monod model was used treating low strength wastewater. Effluent COD concentration was consider as a main predicting factor for performance evaluation. Kinetic constants are obtained by using the equations of completely stirred tank reactor. By comparing the kinetic constant obtained by both two models, kinetic constants are obtained by Monod model is more similar to CSTR model kinetic constants. Maximum percentage error in experimental and predicted effluent COD concentration in Monod model is 25% but in ADM1 model become 30%. From statistical analysis, it is concluded that Monod model is better for performance evaluation in UASB reactor treating low strength wastewater.